Performance measurement in British Helicopter Emergency Medical Services and Australian Air Medical Services. Issue 3 (3rd February 2011) - Simpson, Nicholas; Bartley, Bruce; Corfield, Alasdair R; Hearns, Stephen
Abstract : Background: Performance outcome measures are an essential component of health service improvement. Whereas hospital critical care services have established performance measures, prehospital care services have less well-established outcome measures and this has been identified as a key issue for development. Individual studies examining long-term survival and functional outcome measures have previously been used to evaluate prehospital care delivery. There is no set of standardised patient outcome measures for Helicopter Emergency Medical Services (HEMS) in the UK or Air Medical Services (AMS) in Australia. The aim of this study is to document the patient outcome measures currently in use within British HEMS and Australian AMS. Methods: This is an observational study analysing point prevalence of practice as of November 2009. A structured questionnaire was designed to assess the method of routine patient follow-up, and the timing and nature of applied patient outcome measures. Results: Full responses were received from 17/21 (81%) British services and 6/7 (86%) Australian services. The overall response rate was 82%. Conclusions: HEMS in Britain and Australian aeromedical retrieval services do not have uniform patient outcome measures. Services tend not to follow-up patients beyond 24 h post transfer. Patient outcome data are rarely presented to an external organisation and there is no formal data comparison between surveyed services. Services are not satisfied that the data currently being collected reflects the quality of their service.